The Effect of Menstrual Health Education Adopting the Peer Education Method with the Participation of Mothers on Adolescents' Menstrual Health Behaviors: a Clinical Trial - Reihaneh Jarrahi; Nahid Golmakani; Seyed Reza Mazloom; Hasan Forouzanfar (Mashhad University of Medical Sciences, 2021)
Background & aim: Menstrual health is a major part of adolescent health; nonetheless, the majority of girls do not have sufficient knowledge of menstrual changes. Therefore, current study aimed to assess effect of menstrual health education adopting the peer education method with the participation of mothers on adolescents' menstrual health behaviors. Methods: This randomized clinical trial was conducted on 60 students with regular menstruation in two groups. Two high schools in Mashhad were selected by drawing lots as a random block. In intervention group, at first 10 students received the educational content and then were asked to train 4-7 of their classmates. Mothers of subjects received two 2-hour sessions with the same content. Control group received routine education by a health educator. Data were collected by a valid, reliable self-structured questionnaire of menstrual health behaviors, before intervention and also after the end of  the first and second menstrual cycles and were analyzed in SPSS software (version 16) using  Mann-Whitney, Friedman, and independent samples t-test . Results: Based on the results, mean score of menstrual health behaviors significantly increased in the two groups (p <0.001). However, mean score of menstrual health behaviors in intervention group was significantly higher, compared to the control group (after the end of the first and second menstrual cycles) (p <0.001). Conclusion: peer education with participation of mothers was more effective in enhancement of adolescents' menstrual health behaviors, compared to the traditional routine method. It is recommended that health professionals apply participatory teaching methods for education of health issues, including menstrual health.